Development of the Indonesian Version of the Internet Gaming Disorder Scale (ID-IGDS) - Ifdil, Ifdil; Khairati, Annisaislami; Syahputra, Yuda; Fadli, Rima Pratiwi; Zola, Nilma; Bakar, Abu Yazid Abu (Islamic Guidance and Counseling Journal, 2024)
This study aimed to identify the validity and reliability of the Indonesian version of the Internet Gaming Disorder Scale (ID-IGDS) in measuring Internet gaming disorder. Data were collected from individuals who actively engaged in internet gaming, amounting to a total of 489 teenagers. Rasch analysis was used to examine the unidimensional structure of the scale and its psychometric properties. The results showed that the ID-IGDS has strong validity with an explained variance of 47.8% and good reliability with an item reliability score of 0.99. In addition, there was no significant difference in the results between the sexes in the use of this scale, indicating that the ID-IGDS was used universally without considering the gender factor. This lack of difference can be attributed to the scale’s design, which effectively captures the core behaviors and symptoms of internet gaming disorder that are common to both males and females. Additionally, the items on the scale have been adjusted to be gender-neutral, ensuring that they do not favor one gender over the other.